2022
DOI: 10.1002/aur.2732
|View full text |Cite
|
Sign up to set email alerts
|

Gray matter volume alteration is associated with insistence on sameness and cognitive flexibility in autistic youth

Abstract: Restricted and repetitive behaviors (RRBs) are hallmark characteristics of autism spectrum disorder (ASD). Previous studies suggest that insistence on sameness (IS) characterized as higher-order RRBs may be a promising subgrouping variable for ASD. Cognitive inflexibility may underpin IS behaviors. However, the neuroanatomical correlates of IS and associated cognitive functions remain unclear. We analyzed data from 140 autistic youth and 124 typically developing (TD) youth (mean age = 15.8 years). Autistic you… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 86 publications
1
2
0
Order By: Relevance
“…While cerebellar differences in neuroanatomy have previously yielded inconsistent results in autism (Laidi et al, 2022) and associations with social functioning (Elandaloussi et al, 2023), a large body of research also points to the involvement of cerebellar neuroanatomy and neurocircuitry in the etiology of RRBs in autism (Tian et al, 2022). In line with our findings, autistic individuals with high RRBs were found to have increased GM volume in the vermis VIII and left cerebellar lobule VIII (Seng et al, 2022) and children with complex motor stereotypies have been shown to have increased GM volume in the anterior vermis (Dean et al, 2022). Such structural studies are corroborated by functional work showing for example atypical cerebellar-cortical connectivity being related to elevated RRBs in autistic individuals (Lidstone et al, 2021).…”
Section: Discussionsupporting
confidence: 91%
“…While cerebellar differences in neuroanatomy have previously yielded inconsistent results in autism (Laidi et al, 2022) and associations with social functioning (Elandaloussi et al, 2023), a large body of research also points to the involvement of cerebellar neuroanatomy and neurocircuitry in the etiology of RRBs in autism (Tian et al, 2022). In line with our findings, autistic individuals with high RRBs were found to have increased GM volume in the vermis VIII and left cerebellar lobule VIII (Seng et al, 2022) and children with complex motor stereotypies have been shown to have increased GM volume in the anterior vermis (Dean et al, 2022). Such structural studies are corroborated by functional work showing for example atypical cerebellar-cortical connectivity being related to elevated RRBs in autistic individuals (Lidstone et al, 2021).…”
Section: Discussionsupporting
confidence: 91%
“…The alterations in grey matter volumes in ASD and ID are in line with Seng et al research, emphasizing the relevance of these structural changes to the clinical manifestations of the disorders. [9] The nuanced pattern observed in white matter volumes further refines our understanding, suggesting potential unique characteristics within each diagnostic group.…”
Section: Discussionmentioning
confidence: 83%
“…Understanding neuroanatomical features contributing to neurodevelopmental disorders is a major goal in cognitive and clinical neuroscience. Previous studies have identified cortical morphological differences between individuals with Autism Spectrum Disorder (ASD) and neurotypical controls (NTs), such as cortical thickness (Bethlehem et al, 2020; Hardan, Muddasani, Vemulapalli, Keshavan, & Minshew, 2006; Khundrakpam, Lewis, Kostopoulos, Carbonell, & Evans, 2017; Nunes et al, 2020; Smith et al, 2016; Yang, Beam, Pelphrey, Abdullahi, & Jou, 2016; Zielinski et al, 2014) and gray matter volume (Guo et al, 2021; Hazlett, Poe, Gerig, Smith, & Piven, 2006; Prigge et al, 2021; Sato et al, 2017; Seng, Lai, Goh, Tseng, & Gau, 2022; Yamasaki et al, 2010). Yet, very few have considered tertiary sulci, which emerge last in gestation and show a protracted development after birth (Armstrong, Schleicher, Omran, Curtis, & Zilles, 1995; Chi, Dooling, & Gilles, 1977; Petrides, 2019; Weiner, 2019; Welker, 1990).…”
Section: Introductionmentioning
confidence: 99%